Strategi Artistic Supervision untuk Optimalisasi Pembelajaran di Lembaga Pendidikan - Kholisa Nur Fitria; Sulistyorini, Sulistyorini (Pusat Riset dan Inovasi Nasional, 2026)
Education plays a crucial role in building the foundation of civilization and social welfare, requiring teachers to possess high professional competence to navigate the dynamics of learning in the digital era. This study aims to explore the implementation of artistic supervision as an innovative supervisory strategy to optimize learning, focusing on the development of collaborative relationships, pedagogical innovation, socio-emotional support, constructive feedback, and continuous professional development. The study employed a Systematic Literature Review (SLR) following PRISMA guidelines, reviewing 17 articles from Scopus, Sinta, and Google Scholar published between 2020 and 2025. Qualitative synthesis analysis revealed that artistic supervision fosters harmonious relationships between supervisors and teachers, encourages creativity, and enhances teacher professionalism. Academic and clinical supervision contribute to evaluation, reflection, and constructive feedback supporting ongoing competency development, while the integration of technologies such as Artificial Intelligence and immersive learning enriches learning experiences by increasing personalization and interactivity. The findings confirm that implementing cross-approach supervision strategies can improve learning quality, teacher professionalism, and create an adaptive and inspiring educational environment.